A Meta-Analysis of the Incidence of Adverse Reactions of Statins in Various Diseases - Wanying Li; Ding Wang; Caiyue Lin; Tongze Cai; Mei Zhao; Liuguan Liang; Xingxing Zhao; Xin He; Xiaoyue Liang; Jinghui Zheng (Cardiovascular Therapeutics)
Conclusion: Statins’ adverse reactions differ across populations. For those with hypercholesterolemia and diabetes, statins’ impact on transaminase levels is similar. Yet patients with coronary heart disease, acute coronary syndrome, or acute stroke show varying responses. Notably, myalgia risk in hypercholesterolemia and coronary disease patients using different statins is comparable, but those with acute coronary syndrome or stroke, especially on high-dose rosuvastatin, have a higher myalgia risk.